The Translation of Idiomatic Expressions from English to Indonesian in The Subtitles of The Joker Movie Directed by Todd Phillips - Nurmalia, Lia; Satrio, Rama Febi; Sulistyawati, Meiva Eka Sri; yastanti, unpris (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2024)
The objective of this research is to investigate how idiomatic expressions are translated form English to Indonesian in the Joker Movie to convey the nuanced meanings of the idiomatic expressions. The research uses a qualitative descriptive method. The theories used in this research are Molina and Albir's theory (2002) to analyze the techniques of idiomatic expression translation. Next, the theory form Baker (2018) to analyze the idiomatic translation strategies, and Nida's theory (1982) to analyze the equivalence of this translation. The results show (1) reduction is the dominant technique used in translating idiomatic expression. (2) Two dominant strategies in translating the idiomatic translation are found most of idiomatic expressions are translated to similar meaning and form, and some of the translated to similar meaning but dissimilar form. (3) For the equivalence reaches dynamic equivalent. From the results above the conclusion can be drawn that in translating idiomatic translation reducing an preposition or a word becomes the dominant technique and for the strategies of translating the idiomatic translation in a term of meaning show that most of the idiomatic translation has similar meaning and form while for the equivalence, since idiomatic is very dynamic so dynamic equivalence is reached in idiomatic expression translation.